Comparison Of Red Ginger Dehydration Process Between Oven And Freeze Drying - muhammad zacky rizano; tutun nugraha; vanny narita (Liaison Journal of Engineering, 2022)
As the tendency towards health awareness has increased, the consumption of dried herbs has risen. The phytochemicals within the plant were known for their health benefits. However, dried herbs in the market these days seemed to lack active compounds. The deficiency of active compounds could be evolving from the dehydration process. The research was established to compare thedehydration process in the dried red ginger (Zingiber officinale var. rubrum) production between freeze drying and oven drying. The oven drying process was done by drying in the oven at 60°C for 24 hours. While the freeze‐drying process was done by freezing the red ginger at ‐60°C for 12 hours, then dried in a vacuum at 25°C. Physical appearance, microstructure, chemical constituents,moisture loss, extraction yield, Total Phenolic Content (TPC), and antioxidant activity were analyzed. The results showed that freeze‐dried seemed to have a light green color while the ovendried had a brownish-yellow color. The freeze-dried appeared to have less volume shrinking as the cell wall in the freeze‐dried was more preserved, which was shown by the SEM imaging. GCMS results conveyed that freeze‐dried looked to have more abundant compounds in higher molecular weight. In comparison, the oven-dried had more abundant in lower molecular weight. Also, the results indicated that there was a significant difference between freeze-dried and oven-dried in total phenolic content. However, there were no significant differences in moisture content, extraction yield,and antioxidant activity. Therefore, further research needs to be developed to compare both dehydration processes.Keywords: dehydration, freeze-drying, red ginger, oven drying